Practical Approach for the Preparation of α-Keto Amides by Direct Aminocarbonylation of Carboxylic Esters with a Carbamoylsilane - Han, Yuling; Han, Shenghua; Ma, Jiangwen; Li, Weidong; Chen, Jianxin (Synlett, 2020)
A novel and practical method has been developed for the preparation of α-keto amides by a catalyst-free aminocarbonylation of carboxylic esters with N,N-dimethylcarbamoyl(trimethyl)silane under neutral conditions. A new protocol for the synthesis of vicinal tricarbonyl compounds was also developed by using this method. In the case of diesters, only one ester group reacted selectively with 1.2 equivalents of the carbamoylsilane, leading to the formation of a single α-keto amide. The reaction was suitable for aryl, hetaryl, or open-chain esters containing strongly electron-withdrawing groups.
Keywords: keto amides; esters; carbamoylsilanes; aminocarbonylation; tricarbonyl compounds